Electronic medical records system (EMRS) for Muslim's information and knowledge sharing - Raja Yaacob, Raja Abdullah; Bunawan, Ap-Azli; Jusoff, Kamaruzaman (IDOSI Publications, 2011)
Medical records in electronic forms are seen as an effective way of managing medical records, amidst the increasing number of patient’s population. The role of networking system in increasing the utility of technology leads to the adoption of the electronic medical records (EMR) system. Although the EMR system experiences a slow adoption rate, it promises improved efficiency in the medical and healthcare system by facilitating information exchange among physicians, caring for the same patients. More specifically, the study aims at examining physicians' perceptions towards the importance of various functions of EMR system and the extent to which their characteristics are related to the perceived importance of the functions of the system. Although previous studies suggest that age, computer sophistication and medical speciality of physicians impact the extent to which they use EMR technology, the present study revealed little evidence that these characteristics are related to the perceived importance of EMR functions. This paper describes elements of the electronic medical records (EMR) system that can contribute to the development knowledge and research an as an impetus to the research activities in this area in the Muslim world. It also attempts to consider the various roles that need to be assumed and also reports various strategies that could be undertaken in different capacities such as, government and the business sectors with the goal of adopting an electronic medical records system (EMRS) for the purpose of information sharing.